PERILAKU REPRODUKSI SEHAT REMAJA PADA SISWA MTs NEGERI MODEL DI KOTA PALOPO - Djusmadi Rasyid; Mahriani Mahmud (Voice of Midwifery, 2015)
This research explores issues of adolescent health reproduction behavior mostly occurs in adolescent high school age appropriate with physical and psychological development. At this stage, individuals experience changes physically, psychologically, and socially. Teens characterized by great curiosity, likes to challenge and always wanted to try new things and tend to perform actions without careful thought so that problems experienced are also typical. The general purpose of this research analyzed the factors associated with adolescent health reproduction behavior on MTs Model’s student in palopo city. The research’s design used in this research is a quantitative form using the type of cross sectional approach. From the bivarat analysis in research on MTs Model Palopo’s students founded that message pornographic information (p = 0.002) associated with adolescent health reproduction behavior, the role of the teacher (p = 0.543) was not associated with adolescent health reproduction behavior, the role of parents (p = 0.000 ) associated with adolescent health reproduction behavior and the most factor associated with adolescent health reproduction behavior. Keywords: Health Reproduction, MTs Model’s Student